Bedah Rumah Untuk Kesejahteraan Dan Kesehatan Masyarakat Tidak Mampu Di Gowa Kota Makassar - Djunaedi, Djunaedi; Pannyiwi, Rahmat; Rasyid, Djusmadi; Yulis, Dian Meiliani; Marpaung, Sastrika Handayani (Sahabat Sosial: Jurnal Pengabdian Masyarakat, 2023)
Poverty causes families to be unable to meet the needs of adequate housing for themselves and their families. Not everyone is able to meet their housing needs for economic reasons. One of the basic human needs is a house in the context of decentralized housing provision. Currently, there is no housing provision system in the regions that is responsive to developing needs. This is due to the lack of developed understanding that housing is also a public matter apart from being an individual matter. The aim of implementing the House Renovation Program is targeting poor people who have uninhabitable houses. The house renovation program has had an impact on poverty alleviation in Gowa District, Makassar. Community Service Activities (PKM) by the Indonesian Teachers and Lecturers Association in collaboration with IKAT Japan South Sulawesi as a form of improving the problem of poverty for our underprivileged brothers and sisters with a house renovation program. Apart from alleviating the problem of poverty through this house renovation program, it is hoped that those who receive Mr. Ridwan's assistance will be helped by comfortable accessibility with their families.